Pengaruh Motivasi Kerja Dan Budaya Organisasi Terhadap Kompetensi Pegawai Kementrian Agama Kabupaten Lombok Barat - Muhammad Tohir Hidayat; Mukmin Suryatni; Zainal Abidin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The office of the Ministry of Religion in West Lombok district, totaling 90 people The number of samples used in this study was 90, using the census method. The data collection technique used was a questionnaire in the form of a questionnaire containing questions about work motivation, organizational culture, and competence. The analysis tool used is multiple linear regression analysis using the SPSS 22 for Windows program. The results of the data analysis show that (1) work motivation has a positive and significant effect on employee competence, and (2) organizational culture has a positive and significant effect on employee competence.